Association study of genetic variants on chromosome 7q31 with susceptibility to normal tension glaucoma in a Japanese population - Kato, T (Nature Publishing Group, 2013)
The caveolin 1 to caveolin 2 (CAV1–CAV2) gene region on chromosome 7q31 has been reported to be associated with susceptibility to primary open angle glaucoma (POAG) and normal tension glaucoma (NTG) in previous studies. We investigated whether genetic variants in the CAV1–CAV2 region are associated with NTG in Japanese patients. Two hundred and ninety-two Japanese patients with NTG and 352 Japanese healthy controls were recruited. We genotyped three single-nucleotide polymorphisms; that is, rs1052990, rs4236601, and rs7795356, in the CAV1–CAV2 gene region and assessed the allelic diversity among cases and controls. The frequency of the minor allele (G) of rs1052990 was significantly decreased in NTG cases compared with controls (P=0.014, OR=0.71), whereas NTG or POAG cases had a significantly higher frequency of the allele than controls in previous studies. Conversely, rs7795356 did not show any significant association with NTG cases, and rs4236601 was monomorphic in the Japanese study population. Our findings did not correspond with previous positive results, suggesting that CAV1–CAV2 variants studied in the present study are not important risk factors for NTG susceptibility in all populations. Further studies are needed to elucidate the possible contribution of the CAV1–CAV2 region to the development of glaucoma.